Determination of the Ketoconazole by Green Sequential Injection Spectrophotometry - Saisunee Liawruangrath (2020)
© 2020, © 2020 Taylor & Francis Group, LLC. Ketoconazole was determined by the use of sequential injection analysis (SIA) in tandem with a spectrophotometric detector. This system was designed to interface to a personal computer. The proposed method is based on a coupled redox–complexation reaction, which reduces Fe(III) to Fe(II) by ketoconazole, following by the reaction of Fe(II) with 2,4,6-tripyridyl-s-triazine in an acetate buffer at pH 4.00 at the maximum absorption wavelength of 590 nm. The optimum conditions for the analysis were studied and evaluated. Beer’s law shown to be followed across the concentration range from 0.24 to 5.00 µg mL−1 with a correlation coefficient R2 equal to 0.9962. The relative standard deviation values for the repeatability and reproducibility were less than 1.40% and 2.15% (n = 11) for 2.00 µg mL−1 of ketoconazole. The detection limit (3σ) and limit of quantification (10σ) were 0.07 and 0.24 µg mL−1, respectively. The results for the proposed method and a standard HPLC procedure provided no significant differences (p > 0.05) using Student’s t-test. Therefore, the SIA procedure has been satisfactorily applied to the determination of ketoconazole in pharmaceutical products with a sample throughput of 30 h−1. This study provides an environmentally-friendly analytical tool for quality control in the pharmaceutical industry.